Establishing an Interdisciplinary Compulsory Elective Subject 'Spine' in the Curriculum of the University Study Course of Human Medicine - Zippelius, T; Weschenfelder, W; Eicker, S O; Putzier, M; Röhner, E; Matziolis, G; Strube, P (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2018)
PURPOSE OF THE STUDY Back pain and pathologies of the spine are among the main reasons why people consult a doctor, both general practitioners and paediatricians, as well as, specifically, orthopaedists, surgeons, and neurosurgeons. This involvement of different faculties calls for a high degree of interdisciplinary co-operation. In order to mediate these aspects of spine-specific diagnostics, therapy, and research to students during their studies and to promote up-and-coming specialists, the compulsory elective subject 'Spine' was established. MATERIAL AND METHODS From the winter semester of 2013 to the winter semester of 2014, the compulsory elective subject 'Spine' was offered to interested students in the 7th semester of their studies of human medicine. The maximum number of participants per course was 16. Each course lasted four weeks. The subjects taught covered the fields of degeneration, deformities, and destruction in the specialist disciplines of orthopaedics, traumatology, neurosurgery, and rehabilitation medicine. In addition, orthopaedic technology and the local musculoskeletal and biomechanical research institute were integrated into the course. Various teaching methods were applied, including problem oriented learning, seminars, observation or consultation, and internship. At the end, the course was evaluated with regard to subjective learning success, knowledge gain, satisfaction, and interdisciplinarity. Participants were compared with all students of the semester employing an objectively structured clinical examination (OSCE). RESULTS Forty-eight students took part in the compulsory elective subject 'Spine'. The compulsory elective subject was given a positive rating in all fields. In the learning success control, all of the students had good to very good results. Students attending the elective subject performed significantly better in the objective structured clinical examination (OSCE) (p ≤ 0.001). The compulsory elective course continues to be offered in the curriculum with a slightly altered schedule. CONCLUSIONS In view of the high prevalence of patients with back pain and its associated importance in terms of healthcare policy and social relevance, our experience leads us to recommend the general integration of such a compulsory elective subject in the study of human medicine. Key words:elective subject, spine, students, spinal disorders.
Keywords: ortopedie; Interdisciplinary Communication; Humans; Curriculum; stupeň vzdělání; Biomedical Research; Orthopedics; biomedicínský výzkum; Education, Medical; lidé; Spinal Diseases; studium lékařství; Back Pain; Educational Status; Neurosurgery; bolesti zad; mezioborová komunikace; neurochirurgie; kurikulum; týmová péče o pacienty; Patient Care Team; nemoci páteře